Implementation of the integrated logistics system in the management of business processes - Pavlovskiy, Pavlo (Skhid, 2018)
The article considers the concepts of integrated logistics and its introduction into the economic activity of the processing enterprise. The structure and directions of business processes, which vary depending on the strategic goals and specific subjects of economic activity, are presented. The comparative characteristic of traditional and logistic management of business processes is presented.